Developing Socrative as a grammar assessment platform for senior high school students - Sholakhudin, Farkhan; Wahyuni, Sri; Suci, Dewi Nur; Fitriyah, Ima (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
This research aims to develop an interactive grammar assessment tool utilizing the Socrative platform for eleventh-grade students at MAN 2 Kota Kediri. The instruments used for data collection included a grammar test, validated by experts to ensure content validity, note taking for expert feedback. The Research and Development (R&D) method was employed, grounded in Borg and Gall’s (1983) model and Harris’s (1969) test construction approach, the study followed systematic phases including needs analysis, test design, expert validation, field testing, and item analysis, for its interactive and student-centered nature, which aligns with Deci and Ryan’s (2000) Self-Determination Theory. The developed test consisted of 25 multiple-choice grammar questions delivered via the Socrative platform. Validation results showed that 18 items (72%) were valid, meeting the threshold recommended by Crocker and Algina (2006) for early-stage field use. The reliability of the instrument was high, with a Cronbach’s Alpha coefficient of 0.882. Item analysis revealed that most items had acceptable discrimination power, while the difficulty index showed a predominance of easy items, indicating the need for more balanced test content. The interactive nature of the Socrative platform allows for immediate feedback, fostering student engagement and enhancing grammar comprehension. Additionally, the findings support the use of digital tools like Socrative to create valid, reliable, and engaging language assessments for EFL learners in secondary education.